AskQ logo

STUCK ON HOMEWORK?

ASK FOR HELP FROM OUR KIASUPARENTS.COM COMMUNITY!

Question

Answer

Let M be the amount of money Michael had at first.
Let N be the amount of money Nathan had at first.

M = N + 288
N = M – 288
(1/4)N = (1/4)(M – 288) = (1/4)M – 72 … (1)

(3/8)M – (1/4)N = 150.40 …(2)

Substituting (1) into (2):
(3/8)M – (1/4)M + 72 = 150.40
((3 – 2)/8)M = 150.40 – 72 = 78.40
(1/8)M = 78.40
M = $627.20 #

 

1 Reply 1 Like ✔Accepted Answer

Thanks ChiefKiasu!

0 Replies 1 Like

If Michael had $ 8u at first, Nathan had $ ( 8u – 288). 

After Michael spent 5/8 of his money, he was left with $3u.

After Nathan spent 3/4 of his money, he was left with $ ( 8u – 288)/4 = $ ( 2u – 72).

Given

3u – ( 2u – 72) = 150.4

u + 72 = 150.4

u = 78.4

8u = 627.2

So Michael had $627.2 at first. 

 

 

1 Reply 2 Likes

Thanks waterflow! 

0 Replies 0 Likes